Nazir Wakaf Profesional - Rispan Rispan; Yenni Samri Juliati Nasution (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The issue of nazir waqf, which is still traditional-consumptive due to lack of knowledge about waqf and poor human resources, is one of the obstacles in the implementation of waqf legislation. The problem of naziran will be discussed in this article, along with its definition, tupoksi, professional nazir standards, challenges, and solutions. The findings of this study lead to the conclusion that morality, management, and business, along with other additional information and insights, are necessary for professional nazirs. Professional Nazirs also need to have human skills, technical abilities, and interpersonal skills. Other challenges include expertise, coaching, recruitment, incentives, competencies, and supervision. In addition, the paradigm shift and the existence of Nazir are some of the solutions that can be applied, such as associations, the establishment of Nazir schools, and the improvement of Nazir welfare. The guidance and supervision of Nazir Waqf is carried out by the Minister and the Indonesian Waqf Board, with the aim of improving professionalism and ethics in the management of waqf. Improving the quality of professional nazir is expected to have an impact on increasing the productivity of waqf assets, increasing public trust, and making a real contribution to economic and social development.